Effect of crude palm oil, Aloe vera, glycerol, and starch on characteristics and mechanical properties of polyethylene film / Siti Fatma Abd Karim ... [et al.] - Abd Karim, Siti Fatma; Jai, Junaidah; Ku Hamid, Ku Halim; Abd Jalil, Abdul Wafi (Universiti Teknologi MARA, 2020)
The long-chain structure of polyethylene (PE) have caused low degradation ability of PE, and its hydrophobic nature have reduced its compatibility with other hydrophilic polymer material. This paper focuses on the effect of blending crude palm oil (CPO), Aloe vera (AV), glycerol (G), and starch (S) with PE on the characteristics of PE-based film. The films were prepared using melt blending and hot press techniques to obtain a flat sheet film. The FTIR results have shown that the addition of CPO and glycerol reveal the presence of C=O stretching of the ester group in the PE-based film. The addition of CPO, AV, S-G, and S-CPO reduced the degree of crystallinity of PE-based film by disappearance of 2θ = 21.4774 and 23.7334. Furthermore, the addition of CPO, AV, glycerol, and starch increased the thermal degradation rate of PE-based film, where AV shows the best percentage of weight reduced. The crystallinity of the PE-based film has been disrupted, as shown in the XRD analysis. PE-AV has the highest tensile strength, elongation at break, and lowest Young modulus. In conclusion, AV has better potential then CPO in improving the mechanical properties of PE-based films. Therefore, AV has the ability to become a filler in producing packaging film